Stimulus-dependent processing strategies in the cognitive system: evidence from lexical decision of true- and non-words. - Tiwari S; Krishnan G; Bellur R (Journal of the All India Institute of Speech & Hearing, 2009)
The cognitive models of word processing have gained considerable attention in the recent past. Such models have been successful in explaining a large number of observations in both normal and disordered word processing. Whether the cognitive system employs a serial or parallel processing has been overwhelmingly debated in the field cognitive linguistics. In this context, the present study attempted to investigate the processing capabilities for true words as well as the legal and illegal non-words, using a lexical decision task in a group of normal subjects. The results revealed that the true words were processed faster compared to non-words. In addition, the comparison of lexical decision time for legal and illegal non-words revealed a statistically significant difference between the two sets. We argue that the parallel processing strategy facilitates faster processing and it is employed in the processing of true words while serial processing is employed in legal and illegal non-words. This may be considered as an evidence for the stimulus-dependent processing strategies employed by the cognitive system while processing written stimuli.